Proteínas da fração de membranas do fungo patogênico Paracoccidioides sp. - Curcio, Juliana Santana de (2014)
Paracoccidioides spp. represents thermodimorphic fungi that cause paracoccidioidomycosis, the most widespread systemic mycosis in Latin America. During the establishment of the infection, proteins located in cell membranes are responsible for many essential processes for pathogen survival as transport of nutrients, accession, signaling and energy production. Cell membranes are basically composed of a lipid bilayer with proteins associated. The proteins can be associated with the membrane through transmembrane domains, posttranslational added modifications or through electrostatic interactions. Therefore the knowledge of the constitution of the proteins of membranes is important to understand some processes developed by Paracoccidioides sp. for its growth and survival within the host. To this end, two techniques of separation and identification of proteins were employed. The first methodology used two-dimensional electrophoresis and mass spectrometry, where the extract of membranes proteins was obtained after steps of ultracentrifugation and the second methodology used liquid chromatography coupled with mass spectrometry, to this methodology three protocols were employed to obtain the extract of membranes proteins. The first methodology employed ultracentrifugation, and the second e third methodology used ultracentrifugation/sonication and ultracentrifugation with elevation of pH respectively. After these steps, the extract of membranes proteins was obtained through of ultracentrifugation and elevation of pH with sodium carbonate. Transmission Electron Microscopy (TEM) was performed to confirm the quality of the sample, a fraction enriched in cell membranes of Paracoccidioides sp.. Posteriorly the proteins obtained by standard methodology were subjected to tryptic digestion and analyzed by NanoUPLC-MSE.. In silico analyzes of the identified proteins were performed to determine the location and possible association of the proteins with the cell membranes. From total of proteins identified, one hundred thirty -three proteins were identified as belonging the cell membranes of Paracoccidioides sp.. Eighty-eight proteins showed at least one transmembrane domain and thirteen identified proteins showed a signal peptide at the N-terminus, beyond the transmembrane domain. Different forms of association of the proteins with membranes of Paracoccidioides sp. were detected, including domain transmembrane, GPI anchor, prenylation, myristoylation, palmitoylation. The most of the of integral membrane proteins identified in proteome were annotated in the genome of Paracoccidioides sp. Together these results show the establishment of an experimental protocol for the extraction of membranes proteins of Paracoccidioides spp., as well identify proteins from membrane fractions this fungus.